Hybrid Imaging (PET-Computed Tomography/PET-MR Imaging) of Bone Metastases - Schmidkonz, Christian; Ellmann, Stephan; Ritt, Philipp; Roemer, Frank; Guermazi, Ali; Uder, Michael; Kuwert, Torsten; Bäuerle, Tobias (PET Clinics, 2019)
Bone metastases are a common source of osseous malignancy in the skeleton and affect up to 70% of all cancer patients. Hybrid imaging modalities including positron emission tomography (PET)/computed tomography (CT) and PET/MRI play an increasing role for the detection and follow-up of metastatic disease, especially in monitoring treatment response upon local or systemic therapy. This review summarizes current applications of PET/CT and PET/MRI in the clinical setting for imaging of metastases.
CRIS-Team WoS Importer:2020-02-21